2015
DOI: 10.1001/jamasurg.2014.1242
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Emergent Hernia Repair in the United States

Abstract: These increasing rates of emergent incisional hernia repair are troublesome owing to the significantly increased risk morbidity and mortality associated with emergent hernia repair. While this increased mortality risk is multifactorial, it is likely associated with older age and the accompanying serious comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 19 publications
7
93
2
Order By: Relevance
“…Hernias, particularly umbilical and inguinal hernias, are prevalent among cirrhotic patients due increased intra-abdominal pressure from ascites and abdominal weakness related to hypoalbuminemia and malnutrition (17). Surgical planning for hernia repair is challenging in these patients because they are particularly prone to post-operative complications.…”
Section: Management Of Ventral Hernia Repair In Cirrhotic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernias, particularly umbilical and inguinal hernias, are prevalent among cirrhotic patients due increased intra-abdominal pressure from ascites and abdominal weakness related to hypoalbuminemia and malnutrition (17). Surgical planning for hernia repair is challenging in these patients because they are particularly prone to post-operative complications.…”
Section: Management Of Ventral Hernia Repair In Cirrhotic Patientsmentioning
confidence: 99%
“…[11][12][13][14][15][16] Nationally, the rate of emergency ventral hernia repair increased from 16.0% to 19.2% per 100,000 person-years in 2001 and 2010, respectively (p-value <0.05). 17 Outcomes of emergency surgery are dismal with increased risk of all complications including reoperation (RR 2.72, 95% CI 1.5-4.94), 30-day readmission (RR 1.61, 95% CI 1.23-2.11), and mortality (RR 13.1, 95% CI 6.39-26.86). 18 Alternatively, elective repair in high-risk patients is associated with substantially increased risk for complications.…”
Section: Introductionmentioning
confidence: 99%
“…Gangrene was associated with an increased risk in mortality, consistent with other studies that have examined emergent general surgeries, 19 – 22 but obstruction was not associated with increased mortality within this inpatient population. Previous studies have shown that higher mortality from ED admissions is related to more clinically emergent presentations 1 , 23 . Our analysis adjusted for the presence of such hernia complications as obstruction and gangrene as potential confounders to allow comparison of patients with similar clinical severity between ED admission and elective repairs requiring postoperative inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…More than 750,000 are performed annually, with the lifetime risk of an inguinal hernia being 27% for men and 3% for women 1 , 2 . Even though surgery is the only successful treatment of an inguinal hernia, the decision to operate is determined mostly by the patient’s clinical history and examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation